PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN PADA MOTEL MEXICOLA RESTAURANT SEMINYAK - Ni Kadek Ayu Novita Mawar Sari; Ida Ketut Kusumawijaya (Journal Research of Management, 2022)
This study aims to analyze the effect of service quality and store atmosphere on customer satisfaction at Motel Mexicola Restaurant Seminyak. The data collection technique in this study is a questionnaire. Sampling in this study using purposive sampling method. The respondents taken as samples are people who have been consumers of Motel Mexicola Restaurant with the age of the respondents at least 17 years old with a total of 65 respondents. Based on statistical data analysis, the indicators in this study are valid and reliable. The results of the analysis using multiple linear regression with the regression equation: Y = 1.479 - 0.525X1 + 0.244X2, it can be seen that the two independent variables, namely service quality and store atmosphere, have a positive and significant effect on customer satisfaction at Motel Mexciola Restaurant Seminyak. Judging from the value of R Square = 0.810, this means that the magnitude of the influence of service quality (X1) and store atmosphere (X2) on customer satisfaction (Y) at Motel Mexicola Restaurant Seminyak is 81% while the remaining 19% is explained by other variables which are not researched in this study.